Numerical Simulation of Effluent Discharges Applications with OpenFOAM - Mohammadian, Abdolmajid (Taylor & Francis, 2023)
Discharge Modeling; Numerical Analysis; Desalination; Outfall; Inclined Jets; OpenFOAM; Effluent Dilution Modeling